Kajian Etnobotani Pisang-pisang Liar (Musa spp.) Di Malinau, Kalimantan Timur - Lulut D. Sulistyaningsih; Albert H. Wawo (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
Ethnobotany studies of wild banana species in Malinau, East Kalimantan has been done. There are two varieties of wild banana species in Malinau, e.g. Musa borneensis Becc. var. flavida Häkkinen & Meekiong and Musa acuminata Colla var. microcarpa Nasution. They have an important roles in the customs of the local communities in Malinau, Punan tribes as land certificate. In addition, young pseudostem of M. borneensis Becc. var. flavida often used as food in the traditional parties. The description and the uses of M. borneensis var. flavida and M. acuminata var. microcarpa are presented here.